Life Balance - PhrakruSuntortummanitus; Srikumpa, Rawirot (Journal of Thammawat, 2022)
There are only 4 important aspects of life balance: 1. Doing good 2. Music 3. Sports 4. Academic to help in accepting the overall problem situation. And turn to review by using mind and intelligence to find solutions or solutions for oneself and society, it is the most important thing, life balance is something that will help support or sustain the daily life of people of all sexes, ages and dimensions. To have some problems reduced. Will be the most important practice of life For if one can do it in its entirety, it leads himself to find great happiness and success It’s a perfect life It will also be a good role model for others to follow in the footsteps. Although the economic, social, environmental and information technology situations change.